STUDENTS' PROBLEMS FACE IN ONLINE LEARNING AMIDT PANDEMIC COVID 19 - Joko Prayudha .S (Acitya: Journal of Teaching and Education, 2021)
ABSTRACT The existence of the corona virus requires face-to-face teaching to be replaced with online teaching. As a new alternative in learning, it will certainly bring up several obstacles that will be faced by students while studying. This study aims to determine the difficulties faced by students during online learning by using various applications that support online learning such as WhatsApp, Google Classroom and Zoom Meeting. In this study, qualitative methods have been used and a descriptive approach was used to explain the data. In data collection, questionnaires and interviews were used to obtain in-depth information about the difficulties faced by students during online learning. The results in this study indicate that students experience various kinds of obstacles in the implementation of online learning, such as (1) operating learning applications, (2) limited internet quota, (3), incomplete learning resources / materials, (4) poor communication, and (5) decreased learning motivation during online learning, however, even though there were obstacles faced by the students, it did not stop them from continuing to study in difficult times such as the Covid 19 pandemic.